Risk factors associated with a decreased estimated glomerular filtration rate based on cystatin C levels in school‐age children with extremely low birthweight. Issue 6 (June 2017) - Yamamura‐Miyazaki, Natsumi; Yamamoto, Katsusuke; Fujiwara, Kaori; Santo, Yoko; Michigami, Toshimi; Kitajima, Hiroyuki; Satomura, Kenichi
Abstract: Aim: A single centre retrospective cohort study was designed to investigate the estimated glomerular filtration rate (eGFR) in school‐age children born with extremely low birthweight (ELBW) and to determine risk factors predictive of decreased eGFR. Methods: We compared eGFR based on cystatin C (CysC‐eGFR) between school‐age children born with ELBW (ELBW group, n = 48; median gestational age: 26.9 weeks; median birthweight: 792 g) and children born at term (control group, n = 48). The ELBW group was then further divided into a decreased CysC‐eGFR subgroup (eGFR <90 mL/min per 1.73 m 2, n = 20) and a normal CysC‐eGFR subgroup ( n = 28), and perinatal background factors were compared. Results: The ELBW group showed a significantly lower CysC‐eGFR compared with the control group ( P < 0.001). Comparison between the decreased and normal CysC‐eGFR subgroups in the ELBW group showed that children with lower birthweight, shorter gestational age, lower 5‐min Apgar score, longer length of mechanical ventilation, lower weight gain in the first 11 weeks, chronic lung disease, and postnatal corticosteroid administration had significantly decreased CysC‐eGFR. Multivariate logistic regression showed that a lower 5‐min Apgar score was the only independent risk factor for decreased CysC‐eGFR. Conclusions: CysC‐eGFR might already be decreased at school age in children born with ELBW. Renal assessment in regular follow‐up examinations is recommended. Summary at a Glance: In this manuscript, the authors investigated a highly interesting subject, i.e. the effects of a low birth weight on kidney development. They found that a cystatin C‐ based estimated GFR might already be decreased at school age in children born with ELBW, and concluded that renal assessment in regular follow‐up examinations is recommended for these children.